Experiences of Honours Research Students and Supervisors During the COVID-19 Pandemic: A Pilot Study Framed by Self-Determination Theory - Kumar, Natasha N.; Summerell, Elizabeth; Spehar, Branka; Cranney, Jacquelyn (Frontiers in Education, 2021)
This study evaluated the impact of the COVID-19 pandemic in a sample of Honours students (n=21) and Honours supervisors (n=41) at a major Australian university. Data were collected from voluntary, online, anonymous surveys, which included ratings of the pandemic’s impact on their (a) experience of Honours research activities, and (b) sense of relatedness, competence, autonomy, and wellbeing. Self-determination theory (SDT), which posits that the psychological needs of relatedness, competence, and autonomy lead to a sense of wellbeing, provided a theoretical framework for understanding student and supervisor experience during the pandemic. Both students and supervisors indicated significant impact of the pandemic on the students’ research projects, and the degree of perceived impact did not differ between students and supervisors. There was no relationship between the severity of impact and student or supervisor wellbeing. Student wellbeing was low, but the hypotheses that student SDT needs would not be met were only partly supported. Overall, the extent to which Honours students’ SDT needs were met predicted wellbeing; the outcome was similar for supervisors. Our hypothesis that SDT needs and wellbeing would be higher for supervisors than for students was supported. The theoretical and practical implications of these findings are discussed, including recommendations for Honours programs as we move through the current pandemic.